PENGARUH RETURN ON ASSETS (ROA) DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI MODERASI (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA 2014-2016) - B1031141037, AHMAD NUR ARIEF (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
This study aims to analyze and provide empirical evidence on the effect of return on assets (ROA) and leverage on earnings management with institutional ownership as a moderating variable. Discretionary accruals are used as earnings management proxies and are calculated using the modified Jones model.The research population is 37 consumer goods industry companies listed in Indonesia Stock Exchange (BEI). The research data is secondary data derived from the annual financial report of consumer goods industry companies for the period 2014-2016. Based on purposive sampling method, there are 34 companies that can be used as samples. The analysis technique used in this research is the moderated regression analysis.The result shows that ROA and leverage have no effect on earnings management, and institutional ownership cannot moderate the relationship of ROA and leverage with earnings management.Keywords: Institutional ownership, leverage, earning management, Return on Assets (ROA)